Importance of Accelerated Networking in cloud on Linux VMs - Ratnangi Nirek (North American Journal of Engineering Research, 2022)
Accelerated networking offers a promising solution to enhance the performance of Virtual Machines (VMs) in cloud environments by reducing network latency, increasing throughput, and lowering CPU utilization. This paper presents a detailed case study of implementing accelerated networking on Linux VMs, focusing on its impact on network performance. The study is conducted on a real-world scenario involving a major tech enterprise, highlighting the steps involved, challenges faced, and the performance improvements observed. The findings reveal that enabling accelerated networking can lead to significant enhancements in network performance, making it a valuable practice for enterprises aiming to optimize their cloud infrastructure. This paper aims to provide insights into the implementation process and its benefits, contributing to the existing body of knowledge on cloud computing and network optimization.